عقد الضمان في مادة التأمينات بين الفقه الشرعي والتشريع الجزائري - محمد فوزي بن جاب الله (My University, 2019)
Summary: The Guarantee Contract plays a key role in the vital area of people's activity, as it is important for the economic development of States. This is what made it a symptom of diverse disputes between individuals through repeated attacks on their money, themselves, and their offer. The protection of these rights requires legally guaranteed and legitimate means of ensuring reassurance and stability in transactions between individuals. This has led jurists and legislators to create mechanisms on the basis of which creditors' legal protection is based by regulating the provisions of the security contract. ....................... الملخص: عقد الضمان له دور أساسي في المجال الحيوي لنشاط الأفراد، وذلك لأهميته في تحقيق التنمية الاقتصادية للدول. وهذا ماجعلهعرضةللمنازعات المتنوعة بين الأفراد من خلال الاعتداءات المتكررة على أموالهم، و أنفسهم، و عرضهم. إن حماية هذه الحقوق يتطلب وجود وسائل مكفولة قانونا وشرعا لضمان الطمأنينة والاستقرار في المعاملات بين الأفراد. هذا ما دفع بالفقهاء والمشرعين إلى خلق آليات تقوم على أساسها الحماية القانونية للدائنين من خلال ضبط أحكام عقد الضمان. ...................... Résumé: Le contrat de garantie joue un rôle essentiel dans le domaine vital de l’activité des partculiers pour son importance dans la réalisation du développement économique des pays. Cela l’a rendu vulnérable à divers conflits entre individus à travers de fréquentes représailles sur leur argent, et leurs vies, et leur honneur. La protection de ces droits suppose l’existence de moyens légalement garantis et légitimes pour les assurer. C’est ce qui a poussé les juristes et les législateurs à créer des mécanismes sur la base desquels la protection juridique des créanciers via disposition du contrat de garantie